2019
DOI: 10.1097/phm.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pharyngeal Clearance Maneuver for Initial Tracheostomy Tube Cuff Deflation in High Cervical Tetraplegia

Abstract: Mechanical insufflation-exsufflation, or “cough assist,” is a commonly used method of clearing tracheal and pulmonary secretions in patients with respiratory insufficiency secondary to spinal cord injury. This report presents a novel technique termed the pharyngeal clearance maneuver, which uses a modified application of the mechanical insufflation-exsufflation device to mobilize “secretion burden” at the portion of the trachea above the tracheostomy cuff during cuff deflation. Utilization of this strategy may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Some studies have suggested a reduction in secretion ratings following therapeutic oral trials [21] and respiratory muscle strength training [28]. Ehsanian et al [39] describe a 'cough assist' manoeuvre during tracheostomy tube cuff deflation for therapeutic gain. Certainly, efficacious treatment needs to be informed by improving knowledge of the underlying physiological mechanisms associated with poor secretion management, specifically by determining whether accumulation is due to impaired sensation, ineffective clearance due to motor impairment or a combination of deficits.…”
Section: Future Directionsmentioning
confidence: 99%
“…Some studies have suggested a reduction in secretion ratings following therapeutic oral trials [21] and respiratory muscle strength training [28]. Ehsanian et al [39] describe a 'cough assist' manoeuvre during tracheostomy tube cuff deflation for therapeutic gain. Certainly, efficacious treatment needs to be informed by improving knowledge of the underlying physiological mechanisms associated with poor secretion management, specifically by determining whether accumulation is due to impaired sensation, ineffective clearance due to motor impairment or a combination of deficits.…”
Section: Future Directionsmentioning
confidence: 99%
“…Previous studies have shown that the occurrence of pneumonia in SCI is associated with several factors, such as the severity of paralysis, severity of dysphagia 5 , male sex, presence of chest trauma, delayed intubation 2 , increased tracheal secretion 6 , enteral feeding, and mechanical ventilation 4 . In contrast, nutrition- and inflammation-related indicators have been used to predict surgical risks and postoperative complications 4 , 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%